Arabidopsis PLETHORA transcription factors control phyllotaxis. - Prasad, K; Grigg, S; Barkoulas, M; Yadav, R; Sanchez-Perez, G; Pinon, V; Blilou, I; Hofhuis, H; Dhonukshe, P; Galinha, C; Mähönen, A; Muller, W; et al. (2011)
The pattern of plant organ initiation at the shoot apical meristem (SAM), termed phyllotaxis, displays regularities that have long intrigued botanists and mathematicians alike. In the SAM, the central zone (CZ) contains a population of stem cells that replenish the surrounding peripheral zone (PZ), where organs are generated in regular patterns. These patterns differ between species and may change in response to developmental or environmental cues [1]. Expression analysis of auxin efflux facilitators of the PIN-FORMED (PIN) family combined with modeling of auxin transport has indicated that organ initiation is associated with intracellular polarization of PIN proteins and auxin accumulation [2-10]. However, regulators that modulate PIN activity to determine phyllotactic patterns have hitherto been unknown. Here we reveal that three redundantly acting PLETHORA (PLT)-like AP2 domain transcription factors control shoot organ positioning in the model plant Arabidopsis thaliana. Loss of PLT3, PLT5, and PLT7 function leads to nonrandom, metastable changes in phyllotaxis. Phyllotactic changes in plt3plt5plt7 mutants are largely attributable to misregulation of PIN1 and can be recapitulated by reducing PIN1 dosage, revealing that PLT proteins are key regulators of PIN1 activity in control of phyllotaxis.